The Influence Of Transformational Leadership On Employee Performance With Affective Commitment As A Mediator - Manggiasih Manggiasih; C Budi Santoso (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The objectives of this study was to examine the impact of transformational leadership on employee performance with affective commitment as a mediator. This is a quantitative study employing the techniques of purposive sampling. This study’s data was gathered online, via a Google form distributed to millennial generation employees in Yogyakarta. The obtained data totalled 248 and was analyzed using Partial Least Square (PLS-SEM) to test the hypotheses proposed in this study. According to the findings of this study, transformational leadership has a positive and significant impact on employee performance. The variable of affective commitment fully mediates the effect of transformational leadership on employee performance. This study suggests that organizations should select and develop in leaders who adopt transformational leadership style because they build an inspiration, motivation and loyalty for employee which will in turn enhance their commitment and performance.